Bed agglomeration during biomass fast pyrolysis in a fluidised bed reactor - Burton, Alan Hamilton (Curtin University, 2016)
This thesis explores the previously-unreported phenomenon of bed agglomeration during biomass fast pyrolysis in fluidised bed. Experimental work was carried out to characterise bed agglomerates formed. The differences in bed agglomeration behaviour were also identified among the fast pyrolysis of various mallee biomass components (wood, leaf and bark). A new parameter (sand loading) has also been developed for diagnosing bed agglomeration during biomass fast pyrolysis in fluidised bed under a wide range of conditions.